A Study on Growth and Development of Primary Teacher Education in Assam - Roy, Sumona; Das, Swarnalata (JOURNAL OF INDIAN EDUCATION, 2013)
This study was conducted to find out the growth and development of teacher education at primary level in Assam from 1947 to 2007 in terms of status, number of training institutes, number of trained and untrained teachers, teacher enrolment in teacher training institutes and also initiatives taken by the State in the recent years for improvement of teacher training. Data were obtained from various official records, documentary sources, departmental reports and booklets prepared/published by the Directorate of Elementary and Secondary Educations/DPEP/SCERT office as well as interviews from concerned officials. It was found that in Assam, the percentage of trained teachers rose steadily from 23.03% to 41% and subsequently to 73.11% in 1951, 1961, 1971 respectively. However, the figure declined to 68% in 1981. Responding to this alarming trend, the State has initiated various policies and interventions for qualitative improvement of teacher education since 1986.